Asthma Associated Cytokines Regulate the Expression of SARS-CoV-2 Receptor ACE2 in the Lung Tissue of Asthmatic Patients - Saheb Sharif-Askari, Fatemeh; Goel, Swati; Saheb Sharif-Askari, Narjes; Hafezi, Shirin; Al Heialy, Saba; Hachim, Mahmood Yaseen; Hachim, Ibrahim Yaseen; Mahboub, Bassam; Salameh, Laila; Abdelrazig, Mawada; Elzain, Eman Ibrahim; Al-Muhsen, Saleh; et al. (Frontiers in immunology, 2022)
It is still controversial whether chronic lung inflammation increases the risk for COVID-19. One of the risk factors for acquiring COVID-19 is the level of expression of SARS-CoV-2 entry receptors, ACE2 and TMPRSS2, in lung tissue. It is, however, not clear how lung tissue inflammation affects expression levels of these receptors. We hence aimed to determine the level of SARS-CoV-2 receptors in lung tissue of asthmatic relative to age, gender, and asthma severity, and to investigate the factors regulating that. Therefore, gene expression data sets of well-known asthmatic cohorts (SARP and U-BIOPRED) were used to evaluate the association of ACE2 and TMPRSS2 with age, gender of the asthmatic patients, and also the type of the underlying lung tissue inflammatory cytokines. Notably, ACE2 and to less extent TMPRSS2 expression were upregulated in the lung tissue of asthmatics compared to healthy controls. Although a differential expression of ACE2, but not TMPRSS2 was observed relative to age within the moderate and severe asthma groups, our data suggest that age may not be a key regulatory factor of its expression. The type of tissue inflammation, however, associated significantly with ACE2 and TMPRSS2 expression levels following adjusting with age, gender and oral corticosteroids use of the patient. Type I cytokine (IFN-γ), IL-8, and IL-19 were associated with increased expression, while Type II cytokines (IL-4 and IL-13) with lower expression of ACE2 in lung tissue (airway epithelium and/or lung biopsies) of moderate and severe asthmatic patients. Of note, IL-19 was associated with ACE2 expression while IL-17 was associated with TMPRSS2 expression in sputum of asthmatic subjects. In vitro treatment of bronchial fibroblasts with IL-17 and IL-19 cytokines confirmed the regulatory effect of these cytokines on SARS-CoV-2 entry receptors. Our results suggest that the type of inflammation may regulate ACE2 and TMPRSS2 expression in the lung tissue of asthmatics and may hence affect susceptibility to SARS-CoV-2 infection.